2008
DOI: 10.1111/j.1474-9726.2008.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adipose tissue modulates mammalian longevity

Abstract: SummaryCaloric restriction (CR) can delay many age-related diseases and extend lifespan, while an increase in adiposity is associated with enhanced disease risk and accelerated aging. Among the various fat depots, the accrual of visceral fat (VF) is a common feature of aging, and has been shown to be the most detrimental on metabolic syndrome of aging in humans. We have previously demonstrated that surgical removal of VF in rats improves insulin action; thus, we set out to determine if VF removal affects longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
170
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(178 citation statements)
references
References 8 publications
6
170
2
Order By: Relevance
“…Consistent with the previous reported effects of caloric restriction on ectopic fat deposition (49,50), eat-2(ad465) animals display decreased rate of ectopic lipid storage in pharyngeal muscles compared with their wild-type counterparts during aging (Fig. 4A, B).…”
Section: Longevity-promoting Interventions Alleviate the Rate Of Age-supporting
confidence: 78%
See 2 more Smart Citations
“…Consistent with the previous reported effects of caloric restriction on ectopic fat deposition (49,50), eat-2(ad465) animals display decreased rate of ectopic lipid storage in pharyngeal muscles compared with their wild-type counterparts during aging (Fig. 4A, B).…”
Section: Longevity-promoting Interventions Alleviate the Rate Of Age-supporting
confidence: 78%
“…Affected individuals display greater risk for developing type 2 diabetes, increased inflammation, cognitive impairment, and accelerated functional decline (78,79). Caloric restriction delays or prevents several potentially harmful age-associated phenotypes, which are known to be involved in metabolic syndrome progression (49,50). To this direction, we observed decreased levels of ectopic fat deposition in caloric-restricted eat-2(ad465) mutants compared with wild-type nematodes during aging.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Surgical removal of visceral fat or reduction in adiposity by caloric restriction (CR), are effective strategies in rodents for increasing lifespan and enhancing insulin sensitivity (2)(3)(4). Reducing dietary levels of the essential amino acid methionine also extends lifespan (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, recent studies in mice and in humans have indicated that WAT accumulation could negatively influence longevity, 1,2 whereas a surgical or genetically engineered reduction in WAT mass in rodents could prolong lifespan. [3][4][5][6] This has led various investigators to the postulate that obesity could be considered as a condition of premature metabolic aging. We explored this hypothesis by profiling obesity and agemediated changes in gene expression in visceral WAT using whole-genome microarray technology in mice.…”
mentioning
confidence: 99%